2022
DOI: 10.3390/ijms23073589
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cutibacterium acnes-Mediated Inflammatory Reactions by Fibroblast Growth Factor 21 in Skin

Abstract: Cutibacterium acnes (C. acnes) is a common commensal bacterium that is closely associated with the pathogenesis of acne. Fibroblast growth factor 21 (FGF21), as a favorable regulator of glucose and lipid metabolism and insulin sensitivity, was recently shown to exert anti-inflammatory effects. The role and mechanism of FGF21 in the inflammatory reactions induced by C. acnes, however, have not been determined. The present study shows that FGF21 in the dermis inhibits epidermal C. acnes-induced inflammation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Additionally, inflammation diminishes sulfhydryl groups in the skin, hampering tyrosinase activity and augmenting melanin production. Cutibacterium acnes has been implicated in elevating messenger RNA (mRNA) expression of TNF-alpha, secretion levels of IL-6 and IL-8, mRNA levels of tyrosinase, and dopachrome tautomerase, consequently activating melanocytes and increasing melanin output [15]. A comparative analysis of soluble proteins in pathological sections of acne-induced PIE and PIH revealed elevated levels of dermal remodeling proteases and inhibitors in PIE lesions, indicative of dermal remodeling during excision [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inflammation diminishes sulfhydryl groups in the skin, hampering tyrosinase activity and augmenting melanin production. Cutibacterium acnes has been implicated in elevating messenger RNA (mRNA) expression of TNF-alpha, secretion levels of IL-6 and IL-8, mRNA levels of tyrosinase, and dopachrome tautomerase, consequently activating melanocytes and increasing melanin output [15]. A comparative analysis of soluble proteins in pathological sections of acne-induced PIE and PIH revealed elevated levels of dermal remodeling proteases and inhibitors in PIE lesions, indicative of dermal remodeling during excision [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, here we discuss the role of each of these cytokines in the modulation of skin inflammation and healing. In fact, IL-1β was reported as a potent pro-inflammatory cytokine that is synthesized and released by keratinocytes upon activation of Staphylococcus aureus [ 15 ] and by fibroblast upon activation of Cutibacterium acnes [ 17 ], and its increased levels are related to cell death and damage. The present study showed for the first time that hydrolyzed collagen reduced IL-1β secretion by skin fibroblasts and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TNFAIP3 tempers the inflammation triggered by C. acnes in keratinocytes [ 91 ]. Recent evidence also implicates fibroblast growth factor 21 (FGF21) in exerting anti-inflammatory effects on the epidermal layer [ 92 ]. In keratinocytes, FGF21 acts to mitigate the activation of TLR2, NF-κB, and MAPK signaling prompted by C. acnes [ 92 ].…”
Section: The Regulatory Roles Of Skin Microbiota Particularly ...mentioning
confidence: 99%
“…Recent evidence also implicates fibroblast growth factor 21 (FGF21) in exerting anti-inflammatory effects on the epidermal layer [ 92 ]. In keratinocytes, FGF21 acts to mitigate the activation of TLR2, NF-κB, and MAPK signaling prompted by C. acnes [ 92 ]. Moreover, FGF21 curbs the inflammation driven by C. acnes [ 92 ], suggesting its regulatory role in acne pathogenesis.…”
Section: The Regulatory Roles Of Skin Microbiota Particularly ...mentioning
confidence: 99%
See 1 more Smart Citation